1995
DOI: 10.1111/j.1600-0587.1995.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small‐scale habitat disturbance on the ecology of breeding birds in a Vermont (USA) hardwood forest

Abstract: Lent, R A and Capen, D E 1995 Effects of small-scale habitat disturbance on the ecology of breeding birds in a Vermont (USA) hardwood forest -Ecography 18 97-108We studied territory placement and foraging behavior of breeding birds in relation to juxtaposition of forest vegetation and logged patches in southern Vermont, USA Different bird species used disturbed vegetation at differing spaual scales, depending on temtory size Four species Dendroica pensylvamca. Geothlypis trichas, Zonotrichia albicollii, Oporor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
(14 reference statements)
6
28
1
Order By: Relevance
“…Concomitant with the greater numbers of edge birds, there were fewer forest birds and fewer forest bird species such as winter wrens and Swainson's thrushes. These results are consistent with those from other studies (Askins 1995;Askins and Philbrick 1987;Blair 1996;Blake et al 1994;Bollinger and Linder 1994;Donovan et al 1995a;Hoover et al 1995;Keller and Anderson 1992;Kroodsma 1984;Lent and Capen 1995;Mcintyre 1995;McLellan et al 1986;Stouffer and Bierregaard 1995;Temple and Wilcox Terborgh 1989;Wilcove 1985). However, unlike the previous studies where forested areas were adjacent to developed areas of differing land uses, my findings were conf'med to a forested area contiguous with a city.…”
Section: Breeding Bird Communitycontrasting
confidence: 35%
See 4 more Smart Citations
“…Concomitant with the greater numbers of edge birds, there were fewer forest birds and fewer forest bird species such as winter wrens and Swainson's thrushes. These results are consistent with those from other studies (Askins 1995;Askins and Philbrick 1987;Blair 1996;Blake et al 1994;Bollinger and Linder 1994;Donovan et al 1995a;Hoover et al 1995;Keller and Anderson 1992;Kroodsma 1984;Lent and Capen 1995;Mcintyre 1995;McLellan et al 1986;Stouffer and Bierregaard 1995;Temple and Wilcox Terborgh 1989;Wilcove 1985). However, unlike the previous studies where forested areas were adjacent to developed areas of differing land uses, my findings were conf'med to a forested area contiguous with a city.…”
Section: Breeding Bird Communitycontrasting
confidence: 35%
“…Forest bird species, on the other hand, frequently have specialized habitat requirements and are more sensitive to habitat fragmentation (Lent and Capen 1995;Lynch and Whigham 1984;Whitcomb et al 1981;Wilcove 1985). I found that the richness and abundance of both edge birds and urban birds were greater in edge habitats.…”
Section: Breeding Bird Communitymentioning
confidence: 79%
See 3 more Smart Citations